SOCIAL SECURITY OF THE DAGESTAN POPULATION IN the 1930’S: PROBLEMS AND WAYS OF THEIR SOLUTION - Amirhanova, Madina Magomedovna (History, Archeology and Ethnography of the Caucasus, 2018)
This paper is devoted to the development of the pension system in Dagestan in the 1930s. This problem is an important part of the social policy of the State; because the stability of the society depends on a social population well-being. This research has great scientific significance, because before this other researchers have not studied it. The actual study is mostly based on the new archive materials. In these documents have confirmation that the living standard of the population was low in under study period. The pensions were granted only to the factory and office workers of the State institutions and enterprises and not to the peasants. Also peasants were deficient of social privileges. In archives were found reports that the highly significant progress has been achieved with respect to employment benefits for the blind and deaf in the 1930s. All public institutions and government owned companies in Dagestan were obliged by law to employ disabled people, as vell as provided access to training and retraining when possible. Disabled people were provided with light working professions. The advantage of the mothers of multiple children, order of establishing their state allowance is shown, is also studied. In research was identified the role of the Peasant’s mutual aid Committee in the social welfare for disabled villagers. The discovered documents enriches the general knowledge about the rules of social security of certain categories of the population of Dagestan are studied in this paper.